Generation of Q-switched and mode-locked pulses with Eu2O3 saturable absorber - N.F., Zulkifli; A.A.A., Jafry; R., Apsari; F.S.M, Samsamnun; M., Batumalay*; M.I.M.A, Khudus; H., Arof; S.W., Harun (Elsevier, 2020)
In this paper, Europium Oxide (Eu2O3) is used as a saturable absorber (SA) to produce Q-switched and mode-locked pulses in an erbium-doped fiber laser (EDFL) cavity. The Eu2O3 was synthesized using casting technique and the resulting Eu2O3 thin film was introduced between two optical fiber ferrule connectors to form a SA. Then the SA was positioned in the EDFL ring cavity. A stable Q-switched operation was achieved by controlling the loss and gain of the cavity. As the pumping power was increased from 84.0 mW to 125.0 mW, the repetition frequency increased from 60.1 kHz to 68.6 kHz and pulse width reduced from 4.5 μs to 3.6 μs respectively. The Q-switched EDFL was operating at the center wavelength of 1568 nm, had a 162 nJ maximum pulse energy and 10.24% slope efficiency. Adding a 100 m SMF in the ring cavity initiated a self-starting mode-locked EDFL and the pulses remained stable within a range of 104.6 to 145.8 mW pump power. At the threshold pump power of 104.6 mW, the mode-locked EDFL operated at a central wavelength of 1565 nm with a repetition rate of 1.8 MHz and a pulse width of 3.51 ps. The results show that Eu2O3 can be deployed as a SA for both Q-switching and mode locking generations.